EVOLUTION OF DISCRETE SEMICONDUCTOR COPPER WEDGE BOND IN BIASED TEMPERATURE HUMIDITY CHAMBER (Jurnal Teknologi (Sciences & Engineering), 2022)
The ability to provide electrolyte required in a corrosion process; and its role in facilitating the reaction is widely attributed to humidity. Although corrosion typically develop over time; its symptoms may start showing up much earlier- commonly in the form of degradation. This paper aims at documenting the symptoms- particularly surface morphology of Copper (Cu) wire in discrete semiconductor component as it evolves in a stress-accelerated environment of temperature-humidity chamber. Results gathered from the trial runs show tendencies of Cu wire to degrade in the said environment, with noticeable changes observed on Cu wire wedge bond morphology after completion of 1000 hours in temperature-humidity chamber. Apart from better understanding of how discrete semiconductor with Cu wire behaves in highly demanding end applications like automotive, data obtained also shed some light on the need to reduce probability of material degradation thru better process control and optimization; ultimately in addressing package integrity.